SOC Estimation of an LFP Battery using Extended Kalman Filter with Extracted Prameter - Lim, Hee Sung; Lee, Sang Hyuk; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2023)
This paper proposes a method to estimate SOC(State of charge) by extracting parameters for each circuit element of an LFP(LiFePO4) battery equivalent circuit model and combining the Extended Kalman Filter and coulomb counting method. A lithium battery cell is generally modeled using an equivalent circuit, and parameters for each circuit element of the battery model can be extracted using pulse charging and discharging curves. Those curves are collected experimentally to characterize battery performance at various operating points. Numerical optimization algorithms are repeatedly performed in computer simulation to minimize errors in battery models and experimental data. SOC is estimated using extracted parameters and the Extended Kalman Filter algorithm.
Keywords: Battery; Battery modeling; BMS; Circuit elements; LiFePO4; Modeling; Parameter; SOH; State-of-charge estimation; States of charges; Battery; BMS; Extended Kalman Filter; LFP; LiFePO4; Modeling; Parameter; SOC; SOH